A (DEA) – ; The Data Envelopment Analysis (DEA) for determining the efficiency of a production - Aleksej Lissitsa; Tamara Babiéceva (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2003)
(DEA) - . (Decision Making Unit - DMU), co (output) (input), , (DMU) . DMU, , . . DEA - , , , . Disscusion Paper - DEA, ee . – – The Data Envelopment Analysis (DEA) is a relatively new method to measure Technical Efficiency (TE). TE of a Decision Making Unit (DMU) is defined as a ratio of the produced goods and services (Outputs) to the used resources (Inputs). Efficiency comparison become more complicated when market values of the Inputs and Outputs are not available and the figures are expressed in the different measurement units. So, aggregation of the figures into cost or revenue groups become impossible. Such efficiency analysis is especially important for the enterprises in the transformation process. In DEA the Linear Programming (LP) is used to determine relative efficiency of the analysed enterprises. The basic principles of the DEA are introduced in this Disscusion Paper for the Russian-language reader as well as some further developments are pursued.
urn:nbn:de:gbv:3:2-23263
Keywords: Q12; D2; O1; O4; P3; 650; Efficiency; Produktivity; Data Envelopment Analysis; Data-Envelopment-Analyse; Technische Effizienz; Produktivität; Theorie